PENGETAHUAN DAN SIKAP IBU DALAM PRAKTIK PENCEGAHAN PNEUMONIA DI WILAYAH KERJA PUSKESMAS CILEMBANG KOTA TASIKMALAYA - Fitri, Ai Mawar Rahmawati; Maywati, Sri; Faturahman, Yuldan (Jurnal Kesehatan Komunitas Indonesia, 2025)
Pneumonia is one of the leading causes of under-five deaths due to infection. The role of mothers crucial in prevention efforts, as they play a direct role in caring for maintaning children’s health. Maternal knowledge and attitudes are factors that influence the practice of pneumonia prevention in toddlers. This study aims to determine the relationship between knowledge and attitudes towards mothers’ practices in preventing pneumonia in toddlers in the Cilembang Health Center working area of Tasikmalaya City. This study used cross sectional design with a quantitative approach. The population in this study were mothers mothers of pneumonia toddlers aged 1259 months with a total sample of 114. Sampling used purposive sampling technique. The data collection technique was through interviews and quistionnaires. The result of univariat data analysis showed that 74,6% of mothers had good knowledge, 77,2% had positive attitudes, and 78,1% had good prevention practices. Chi Square statistical test result showed that there was a significant relationship between knowledge and practice (p=0,008) and between attitude and practice (p=0,000). In conclusion, is a significant relationship between mother’ knowledge and attitude with the practice of pneumonia prevention in toddlers in the Cilembang Health Center working area of Tasikmalaya City. Suggestions for mothers are to be more active in attending health counselling at the posyandu or health center, and to seek information from health workers on how to prevent pneumonia infection in children.